2018
DOI: 10.1111/jcmm.13785
|View full text |Cite
|
Sign up to set email alerts
|

Dual effects of baicalin on osteoclast differentiation and bone resorption

Abstract: Osteoclasts (OC) are critical cells responsible for many bone diseases such as osteoporosis. It is of great interest to identify agents that can regulate the activity of OC to treat osteolytic bone diseases. In this study, we found that baicalin exerted a two‐way regulatory effect on OC in a concentration‐dependent manner in vitro and in vivo. In detail, baicalin at a low concentration (below 1 μmol/L) enhanced OC differentiation and bone resorption, but baicalin at a high concentration (above 2 μmol/L) exhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…3,4 Previous researchers have focused on the pathological mechanisms of osteoclasts formation. [5][6][7][8] However, few studies have shown the increased accumulation of macrophages at the beginning of wear particles. The macrophage cells are then further differentiated into osteoclasts with bone resorptive function.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Previous researchers have focused on the pathological mechanisms of osteoclasts formation. [5][6][7][8] However, few studies have shown the increased accumulation of macrophages at the beginning of wear particles. The macrophage cells are then further differentiated into osteoclasts with bone resorptive function.…”
Section: Introductionmentioning
confidence: 99%
“…Luteolin also suppresses the mitochondrial apoptosis of osteoblasts via inhibition of STAT1 activity [ 73 ]. Moreover, baicalin was shown to be therapeutic for osteoclast-related bone diseases through the inhibition of the NF-κB and ERK pathways [ 74 ]. Baicalein can stimulate osteoblast differentiation via the activation of the mTORC1 signaling pathways, including the P-S6K1 and P-4E/BP1 transcription factors [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are two sclerostin inhibitors, romosozumab and baicalin; romosozumab is a human monoclonal antibody against sclerostin (45), and baicalin, a herb-derived flavonoid compound, binds to sclerostin via hydrophobic interactions with the amino acid residues on loop2 region, but outside the Pro-Asn-Ala-Ile-Gly motif, particularly the Arg-Gly-Lys-Trp-Trp-Arg motif (46). The beneficial effects of these two agents against osteoporosis have been reported in a number of studies (47)(48)(49)(50). Although the effect of romosozumab on cardiovascular events including VC is controversial (45,51), baicalin has been reported to relax VSMCs (52), ameliorate atherosclerosis (53), prevent trans-differentiation of VSMCs (54) and inhibit vascular remodeling (55), via which baicalin may ameliorate VC.…”
Section: Discussionmentioning
confidence: 99%